2014
DOI: 10.1371/journal.pone.0097555
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of a Prednisolone Acetate-Loaded Subconjunctival Implant for the Treatment of Recurrent Uveitis in a Rabbit Model

Abstract: AimTo assess the efficacy of a biodegradable, prednisolone acetate implant in a rabbit uveitis model.MethodsRandomized, controlled study of biodegradable microfilms preloaded with prednisolone acetate (PA) in a rabbit uveitis model. Experimental uveitis was induced by unilateral intravitreal injection of Mycobacterium tuberculosis H37Ra antigen (50 ug; 1 ug/uL) in preimmunized rabbits. PA-loaded poly[d,l-lactide-co-ε-caprolactone] (PLC) microfilms (n = 10) and blank microfilms (n = 6) were implanted subconjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
2
24
0
1
Order By: Relevance
“…In this approach, the BT‐loaded M/CS may be implanted in the subconjunctiva, and may be periodically replaced when the BT release is complete (Figure S1, Supporting Information). Subconjunctival implants have been previously used to deliver drugs for conditions such as uveitis and glaucoma for extended periods of up to 1 month without damage to surrounding tissue . Biodegradable polymer films have also been implanted in the subconjunctiva for up to 6 months without surrounding tissue damage or inflammation, confirming the safety of the subconjunctival location for long‐term implantation.…”
Section: Introductionmentioning
confidence: 90%
“…In this approach, the BT‐loaded M/CS may be implanted in the subconjunctiva, and may be periodically replaced when the BT release is complete (Figure S1, Supporting Information). Subconjunctival implants have been previously used to deliver drugs for conditions such as uveitis and glaucoma for extended periods of up to 1 month without damage to surrounding tissue . Biodegradable polymer films have also been implanted in the subconjunctiva for up to 6 months without surrounding tissue damage or inflammation, confirming the safety of the subconjunctival location for long‐term implantation.…”
Section: Introductionmentioning
confidence: 90%
“…16 We further loaded the PLC microfilms with prednisolone acetate (PA) and demonstrated that the PA microfilms significantly reduced corneal graft rejection after corneal transplantation, 17 reduced postoperative inflammation and prolonged bleb survival following glaucoma filtering surgery, 18 and suppressed the severity of uveitis in animal models. 19 We have also loaded the PLC microfilms with timolol maleate and demonstrated the sustained intraocular pressurelowering effects. 20 In the present study, we aimed to evaluate the efficacy of the biodegradable, tacrolimus-loaded PLC drug delivery system on allergic conjunctivitis using a mouse model.…”
mentioning
confidence: 90%
“…Ang (2014) has developed prednisolone acetate-loaded PCL microfilms to be implanted subconjunctivally for uveitis treatment and has reported that the formulation was effective in a rabbit uveitis model (Ang 2014). Wong (1989) published a patent (US 7846468) for immunosuppressive biodegradable ocular implants using PLGA and HPMC against transplant rejection.…”
Section: Ocular Inserts and Implants For Anterior Segment Diseasesmentioning
confidence: 99%